(untitled) (Lex localis - Journal of Local Self-Government, 2012)
This article is concerned with the political careers of local councillors. More specifically, the key question is about a possible professionalization of councillor careers at the local level in Europe. If the careers of local councillors tend to follow a number of standard routes, to what degree can these be perceived of as professionalized? In our effort to identify dominant courses of mobility, we distinguish between three successive stages of councillor careers: Pre-electoral experiences, in-council orientations, and future career aspirations. In the ideal model of professionalization there is a strong link between career stages. Professionalization is seen as a unidirectional process by which an occupational group gradually acquires the traits of a profession. By and large, local political careers in European countries do not adhere to the linear model of professionalization. Instead, a fits-and-start model seems more suitable, indicating that professional careers to a large extent are shaped incrementally, through learning and practical experience.